Implementation of a Profit Website and Introduction of IoT Technology to Support Business Decision-Making for MSMEs in Plaosan Village - Ida Wahyuni; Samsul Arifin; Nur Lailatul Aqromi; Philip Faster Eka Adipraja; Siti Nurul Afiyah; Rina Dewi Indahsari; Mime Azrina Jaafar; Nur Farhana Mustahidin; Khairul Anuar Ishak; Isyati Binti Suparman; Mohd. Sahran@Awang Bin Mohidin (International Journal of Community Service (IJCS), 2026)
Digital transformation in the agricultural Micro, Small, and Medium Enterprises (MSMEs) sector is crucial for enhancing the economic competitiveness of rural communities. Plaosan Village in Malang Regency, a producer of Mount Kawi coffee, faces challenges in financial management and agronomic efficiency. This community service program aims to: (1) implement the “Hitung Profit Kopi” web application (https://indowhiz.com/kopikawi) as a Decision Support System (DSS) for calculating farming profitability; and (2) introduce Internet of Things (IoT) concepts for post-harvest quality control. The program consisted of needs assessment, website design and testing, hands-on training on website use, and lectures plus demonstrations of an IoT prototype. Evaluation used short pre- and post-tests, satisfaction questionnaires, and observation of participants’ engagement during practice sessions. The results show that participants were able to operate the profit website, input their own business data, and interpret the calculated outputs. Furthermore, participants’ understanding of IoT and its potential applications increased, as indicated by improved post-test scores and feedback. This program represents an initial step towards the digital transformation of MSMEs in Plaosan Village through data-driven business management.